Analysis of Female Labor Participation in Increasing Family Income in Simalungun Regency - Sintia Afriani (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2020)
The participation of women in increasing family income by working is commonplace, women not only act as housewives, but also can work to help their husbands to increase their income. Pematang Kerasa Village is one of the areas with more female population than male population. Where many women in Pematang Kerasa Village work to help their husbands in increasing family income, this is because the husband's income is uncertain, insufficient, or even has no income at all. This study aims to determine whether or not there is a simultaneous and partial influence of age, education, working hours and the number of dependents on the participation income of women workers in Pematang Kerasa Village, Bandar District, Simalungun Regency. As well as knowing the contribution of women workers' participation income to total household income. The method used in this study is to use the Multiple Linear Regression method with a probability sample design with a sample size of 94 people, where the respondents studied were female workers who participated in increasing family income in Pematang Kerasa Village. The results showed that the income function model for the participation of female workers in Pematang Kerasa was: Y= 2595.584 + 14525.573U + 66874,858P + 47531.455Jk +388444,529M. Taken together, it was found that all the variables studied were age, education, working hours and number of dependents have a positive and significant effect on the participation income of women workers in Pematang Kerasa Village, Bandar District, Simalungun Regency. Meanwhile, the contribution of the participation income of women workers in Pematang Kerasa Village to the total family income is 48.45%.